The Solid Influence of Spread on the Growth and Survival Rate of Sea Worm's (Nereis sp.) - Rajuansah Rajuansah; Muhammad Junaidi; Bagus Dwi Hari Setyono (Jurnal Biologi Tropis, 2021)
Nereis sp. including one of the commodities that have high economic value as well as important commodities in the world of aquaculture. The survival rate of organisms affected by good cultivation management include solid spread, feed quality, water quality, parasites or diseases. High spread solids will have an impact on the decrease in growth rate, feed consumption and survival rate. Therefore, the importance of research on solid spread because it is very closely related to the production and growth speed of cultivated biota. This study was conducted to find out the influence of different scatter solids on the growth and life's smoothness Nereis sp. The research was conducted for 35 days of maintenance using marine worm biota or Nereis sp. The method used is an experimental method using a Complete Randomized Design (RAL) with 5 treatments and 3 repeats namely, Treatment 1: solid spread 50 individuals/m2, Treatment 2: solid spread 100 individuals/m2, Treatment 3: solid spread 150 individuals/m2, Treatment 4: solid spread 200 individuals/m2 and Treatment 5: solid spread 250 individuals/m2. Treatment with solid spread 150 individuals / m2 (P3) gives the best influence in improving the growth and survival of Nereis sp. 0.7838 g and 93.33%.